Delivering the digital restaurant the path to digital maturity - Sandland, Meredith ([Place of publication not identified] Independently Published, 2023)
"The duo that explained the digital revolution in restaurants now brings your restaurant a how-to guide. The digital restaurant revolution is well underway. Restaurants that survived the pandemic now have the opportunity to step back and consider how to best serve digital demand.


Delivering the Digital Restaurant: Your Roadmap to the Future of Food sets out why restaurateurs worldwide must treat digitization and the off-premise channel seriously. Combining interviews with technology and restaurant leaders, the authors articulated why this growth channel was critical for restaurants to survive.


Indeed, the Covid-19 pandemic separated digital leaders from all others. Those who invested in digital guest relationships and the operations that enable them leaped ahead–with 2022 revenues well in excess of 2019. Those who didn’t treat it seriously perished and never reopened. A great many restaurants fell somewhere in the middle–they added digital elements out of necessity but did not update their restaurant operations to match their new capabilities. Or perhaps they tacked on several different digital approaches but did not integrate them.


The story of the first book was incomplete. The Path to Digital Maturity completes the story through a journey toward digital maturity. With the pandemic increasingly in the rearview mirror, now is the time for restaurants to find their current place on the path and follow it toward a more prosperous future. This playbook charts the way. Knowing where you are now lets you determine where you can ultimately be. This new book outlines how to evolve and grow stronger in off-premise channels." --
Be found -- Convert fans -- Mine data -- Optimize throughput -- Grow topline -- Be guest-centric -- Disrupt yourself -- Holistic technology.
Includes bibliographical references.
Keywords: Orsbourn, Carl; Restaurants -- Technological innovations; Restaurants -- Marketing; Restaurant management -- Data processing; Restaurant management -- Electronic commerce